Case report: Uncommon manifestations of Rosai-Dorfman disease in the liver mimicking HCC - Ren, Huipeng; Zhang, Hao; Wan, Qinyun; Pang, Yuhui; Tian, Hongzhe; Ren, Zhuanqin; Cai, Yuan (Frontiers in Oncology, 2024)
Rosai-Dorfman-Destombes disease (RDD) is a rare non-Langerhans cell histiocytosis (LCH) disorder characterized by systemic extranodal lesions. Common cases include skin lesions, whereas liver lesions are rare. This study presents a case of a 66-year-old woman with a solitary extranodal liver lesion who underwent successful surgical treatment followed by glucocorticoid therapy. The patient did not experience any symptoms before surgery. The liver lesion was incidentally discovered during a routine ultrasound examination. Enhanced CT scan revealed the lesion with the characteristic of washout, similar to primary hepatic cancer (HCC). CT scans of the head, neck, chest, and abdominal pelvis revealed no lymph node or other organ lesions. After surgery, the liver lesion was diagnosed as RDD, and subsequent whole-body examinations did not reveal any skin lesions. The definitive diagnosis was solid liver RDD in adults. Although there were no typical cases of bilateral cervical lymph node lesions, ultrasound and CT examinations promptly detected liver lesions, leading to the correct diagnosis through surgical resection. The findings from this case indicate that RDD can occur in rare extrasegmental areas, and the imaging characteristics of liver lesions are not specific, indicating the importance of avoiding delayed diagnosis.